DEVELOPING CONCEPTUAL AWARENESS OF THE FUTURE PROFESSION IN THE STUDENTS OF INTERNATIONAL RELATIONS THROUGH FLT - L. P. Kostikova (Vestnik MGIMO-Universiteta, 2013)
The article is devoted to the issues of professional language training of the students majoring in International Relations. Conceptual awareness of the future professional activity of a specialist in international relations is presented as a part of the new modern professional training paradigm. It is shown that there are various effective ways of preparing students for intercultural communication in professional discourse in the process of teaching and learning a foreign language. A matter of great importance is to develop for students the conceptotermino- systems in questions of international politics, economics, science and war technologies, humanitarian, ideological and international issues of culture and education. This multisided process is complex, value-determined, social, practically-oriented, culturally focused. The author proposes a system of pedagogical support for this process which is based on the integration of different kinds of educational activity: study, research and social activities. All this should work at different levels, that of an individual, group, department, university, cooperation between universities either within the country or in different countries of the world. The ideas of life-learning education should also be carefully developed in this respect. The importance of the student-centered teaching is shown. The leading role of MGIMO(U) educationalists in the professional language training development is accepted.